Ball speed predictors in one-legged attacks in female volleyball players - Stefanovic, T. (Point Loma Nazarene University, 2022)
Previous literature in volleyball biomechanics highlighted jump height and ball speed as key determinants for the success of regular spikes. To further current research and provide athletes and coaches with direct parameters for proper execution of more complex volleyball attacks, ball speed predictors of a slide attack were investigated. Healthy collegiate female volleyball players (middle blockers, pin hitters), actively participating in volleyball were recruited. After a warm-up, 3 successful slide attacks per participant were recorded using an 8-camera motion capture system, while a radar gun was used to measure the ball speed upon contact. The trial with the fastest ball speed was selected for further analysis, where COM approach speed, maximum velocity of pelvis and torso in the arm cocking phase, and maximum velocity of torso, shoulder, and elbow during the arm acceleration phase were calculated. It was hypothesized that a combination of these variables will help reliably predict the ball speed in slide attacks. Although not statistically significant, the findings indicate that peak torso velocity in the arm cocking phase and peak shoulder and peak elbow velocities in the arm acceleration phase are important contributors to the ball speed in slide attacks. Still, the most influential contributor to the ball speed is peak torso velocity during the arm cocking phase.